Bioconversion of egg cholesterol to pro-vitamin D sterols with Tetrahymena thermophila - Valcarce, G. (2002)
The potential use of the non-pathogenic ciliate Tetrahymena thermophila for converting cholesterol into pro-vitamin D sterols in egg suspensions was investigated. Conditions screened for efficient conversion included inoculum size and age, egg and egg yolk dilution, initial pH, and aeration. By optimizing these parameters, 55% ± 6 cholesterol reduction was obtained in 24 hours incubation. Tetrahymena converted cholesterol into three unsaturated sterols, D7, 22 bis-dehydrocholesterol, an ergosterol analog (27%), D7-dehydrocholesterol, also known as pro-vitamin D3 (4%), and A22- dehydrocholesterol (8%). Despite significant proteolysis, culturing with Tetrahymena did not result in net consumption of total amino acids content, which was in fact increased by 16% ± 2. These findings emphasize the potential use of Tetrahymena in the food industry.